Answer:
2.56 m/s
Step-by-step explanation:
The change in the momentum is equal to the force times time. So, we have the following equation
![\begin{gathered} \Delta p=Ft \\ mv_f-mv_i=Ft \end{gathered}](https://img.qammunity.org/2023/formulas/physics/college/b2hepbdy5zfdzsk65mv2p150o6t09iu0wv.png)
Where m is the mass, vf is the final velocity, vi is the initial velocity, F is the force and t is the time. Solving for vf, we get:
![\begin{gathered} mv_f=Ft+mv_i \\ \\ v_f=(Ft+mv_i)/(m) \end{gathered}](https://img.qammunity.org/2023/formulas/physics/college/t07hmqk03poib6xmvuihl7vvzfaszmon96.png)
Now, we can replace F = 662N, t = 0.24 s, m = 62 kg, and vi = 0 m/s.
Then, the final velocity is
![\begin{gathered} v_f=\frac{(662N)(0.24s)+(62\text{ kg\rparen\lparen0 m/s\rparen}}{62\text{ kg}} \\ \\ v_f=2.56\text{ m/s} \end{gathered}](https://img.qammunity.org/2023/formulas/physics/college/vvp9duudq5zdpcb9a3yeg3suht42of45bx.png)
Therefore, the answer is 2.56 m/s